2008
DOI: 10.1111/j.1462-2920.2008.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of aerobic anoxygenic phototrophs in temperate freshwater systems

Abstract: The presence of aerobic anoxygenic phototrophs (AAPs) was recently reported from various marine environments; however, there is little information regarding their distribution in fresh waters. We surveyed a number of freshwater systems in central Europe, by infra-red fluorometry, infra-red epifluorescence microscopy, fluorescence emission spectroscopy and pigment analyses. AAPs were found to be abundant in several oligotrophic and mesotrophic lakes (50-400 ng of bacteriochlorophyll a l(-1), 10-80% of bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
92
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 34 publications
14
92
0
Order By: Relevance
“…In contrast, various reports showed that these organisms are abundant in eutrophic as well as in oligotrophic environments (Jiao et al, 2007;Koblížek et al, 2006;Yutin et al, 2007). Other authors suggested that nutrient concentrations (Mašín et al, 2008), attachment to particles Waidner and Kirchman, 2007) or light intensity (Koblížek et al, 2003;Shiba, 1991) may influence AAP bacterial abundance.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…In contrast, various reports showed that these organisms are abundant in eutrophic as well as in oligotrophic environments (Jiao et al, 2007;Koblížek et al, 2006;Yutin et al, 2007). Other authors suggested that nutrient concentrations (Mašín et al, 2008), attachment to particles Waidner and Kirchman, 2007) or light intensity (Koblížek et al, 2003;Shiba, 1991) may influence AAP bacterial abundance.…”
mentioning
confidence: 75%
“…It has been hypothesized that the capacity of AAP bacteria to generate energy from light could reduce the metabolic requirements for recycling the organic carbon resources (Cho et al, 2007). Mašín et al (2008) suggested that light-generated energy could enhance P acquisition in P-depleted environments. On the basis of our nutrient-addition experiments, we cannot speculate about P-limitation of AAP bacteria since growth of AAP and total prokaryotes were not stimulated by P addition, although higher heterotrophic bacterial activity was observed.…”
Section: Bacterial Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given their capability of harvesting light energy, they represent an important fraction of the bacterioplankton in freshwater and marine illuminated environments (Kolber et al, 2000(Kolber et al, , 2001Béjà et al, 2002;Jiao et al, 2007;Yutin et al, 2007;Masin et al, 2008;Jiang et al, 2009). AAP bacteria were found to be widely distributed in the marine environment representing about 1.5-5 % of total bacteria in the euphotic zone of the ocean (Schwalbach and Fuhrman, 2005;Cottrell et al, 2006;Sieracki et al, 2006;Jiao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic anoxygenic phototrophs (AAP; belonging to Alpha-and Gammaproteobacteria) have been described for marine habitats and more recently for freshwater systems (Page et al 2004, Gich & Overmann 2006. Masin et al (2008) reported on the important and widespread distribution of such phototrophs (containing bacteriochlorophyll a) in freshwater environments. They are obligate aerobes because they require oxygen for respiration and growth.…”
Section: Bacteria Related To the Main Biogeochemical Cyclesmentioning
confidence: 99%